2015
DOI: 10.1016/j.freeradbiomed.2015.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant cytoprotection by peroxisomal peroxiredoxin-5

Abstract: Peroxiredoxin-5 (PRDX5) is a thioredoxin peroxidase that reduces hydrogen peroxide, alkyl hydroperoxides, and peroxynitrite. This enzyme is present in the cytosol, mitochondria, peroxisomes, and nucleus in human cells. Antioxidant cytoprotective functions have been previously documented for cytosolic, mitochondrial, and nuclear mammalian PRDX5. However, the exact function of PRDX5 in peroxisomes is still not clear. The aim of this work was to determine the function of peroxisomal PRDX5 in mammalian cells and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…The plasmid encoding the cytosolic (cyto)-human glutaredoxin 1 (Grx1)-roGFP2 was obtained by amplifying the cDNA Grx1-roGFP2 sequence without the Peroxisomal Targeting Sequence 1 (PTS1) from the plasmid encoding the peroxisomal (po)-Grx1-roGFP2 vector [19] by PCR (primers; pCyto-EcoRI-5′ 5′-gga gga gga tca gga gga gaa ttc gtg agc aag ggc gag gag-3′ (forward) and pCyto-XbaI-3′ 5′-ctc gac tta tct aga tta ctt gta cag ctc gtc-3′ (reverse)) and subcloned into PCR2.1-TOPO (Invitrogen). The resulting plasmid was digested with EcoRI and XbaI, prior to subcloning into the EcoRI/XbaI digested pcDNA3.1-Grx1-roGFP2-PTS1 vector to obtain the p-cyto-Grx1-roGFP2.…”
Section: Methodsmentioning
confidence: 99%
“…The plasmid encoding the cytosolic (cyto)-human glutaredoxin 1 (Grx1)-roGFP2 was obtained by amplifying the cDNA Grx1-roGFP2 sequence without the Peroxisomal Targeting Sequence 1 (PTS1) from the plasmid encoding the peroxisomal (po)-Grx1-roGFP2 vector [19] by PCR (primers; pCyto-EcoRI-5′ 5′-gga gga gga tca gga gga gaa ttc gtg agc aag ggc gag gag-3′ (forward) and pCyto-XbaI-3′ 5′-ctc gac tta tct aga tta ctt gta cag ctc gtc-3′ (reverse)) and subcloned into PCR2.1-TOPO (Invitrogen). The resulting plasmid was digested with EcoRI and XbaI, prior to subcloning into the EcoRI/XbaI digested pcDNA3.1-Grx1-roGFP2-PTS1 vector to obtain the p-cyto-Grx1-roGFP2.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, targeted variants of KillerRed, a red fluorescent photosensitizer that efficiently generates O 2 •− upon green light illumination [131], have been employed to study redox communication between peroxisomes and mitochondria in mammalian cells [108,132,133]. On one hand, these studies confirmed and extended the concept that mitochondrial redox balance is quickly perturbed upon generation of excess ROS inside peroxisomes.…”
Section: Interorganelle Signalingmentioning
confidence: 97%
“…On one hand, these studies confirmed and extended the concept that mitochondrial redox balance is quickly perturbed upon generation of excess ROS inside peroxisomes. On the other hand, they provided the first evidence that (i) peroxisomes largely resist oxidative stress when the burden originates within mitochondria [108]; and (ii) redox communication between peroxisomes and mitochondria involves complex signaling pathways [132,133]. Importantly, although the identity and mechanisms of these pathways remain to be elucidated (and may differ according to the type and amount of ROS produced), the data presented in this section strongly support the idea that mitochondria may act as dynamic receivers, integrators, and transmitters of peroxisome-derived mediators of oxidative stress [132].…”
Section: Interorganelle Signalingmentioning
confidence: 99%
“…As already mentioned above, SOD1 can convert O (Knoops et al, 2011). GSTK1 and MGST1 are thought to play a role in LOOH detoxification processes Johansson et al, 2010;Wang et al, 2013b), EPHX2 can convert epoxides to the corresponding dihydrodiols (Decker et al, 2009), and peroxisomal PRDX5 has recently been shown to exert a cytoprotective function against H 2 O 2 -and LOOH-induced oxidative stress (Walbrecq et al, 2015). For a detailed description of these enzymes, the reader is referred to other reviews .…”
Section: Antioxidant Systemsmentioning
confidence: 99%